Flora of Rambha Rural Municipality, Palpa, Nepal - Regmi, Sushma; Koirala, Umesh (Nepalese Journal of Biosciences, 2017)
The floristic study was conducted in Rambha Rural Municipality 1 Hungi, Palpa, Nepal to explore and document flowering plants. In this study, altogether 92 plant species were identified under 84 genera and 43 families. The study area was dominated by Lamiaceae (11 sps) followed by Leguminosae (10 sps), Euphorbiaceae (6 sps) and Anacardiaceae and Poaceae (5 sps each).